Change in meaning and the meaning of change. Matti Rissanen - Marianna Hintikka - Leena Kahlas-Tarkka - Rod McConchie (eds.) - Molencki, Rafał (Studia Anglica Posnaniensia, 2012)
Review: Matti Rissanen, Marianna Hintikka, Leena Kahlas-Tarkka, Rod McConchie (eds.). 2007. Change in meaning and the meaning of change: Studies in semantics and grammar from Old to Present-Day English. Mémoires de la Société Néophilologique de Helsinki LXXII. Helsinki: Société Néophilologique. Pp. xvii